2016
DOI: 10.1089/omi.2016.0133
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Knowledge on Very Important Pharmacogenes CYP2C9 and CYP2C19 Variation for Precision Medicine in Resource-Limited Global Conflict Zones

Abstract: Pharmacogenomics harnesses the utility of a patient's genome (n = 1) in decisions on which therapeutic drugs and in what amounts should be administered. Often, patients with shared ancestry present with comparable genetic profiles that predict drug response. However, populations are not static, thus, often, population mobility through migration, especially enmasse as is seen for refugees, changes the pharmacogenetic profiles of resultant populations and therefore observed responses to commonly used therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They are intended for the visualization of the complexity of ethnic categorization in pharmacogenetics literature and only reflect how these ethnic categories were classified in the literature we reviewed. A full list of ethnic categories included in this study can be found in Table S2 .
Figure 1Chart of ethnic categories which fall under the NIH term of “Asian”. Note: Data from references 7, 8, 10, 12, 14, 16, 28, 37, 41, 42, 48, 51, 7173, 8790.
Figure 2Chart of ethnic categories which fall under the NIH term of “Caucasian”. Note: Data from references 9, 11, 13, 18, 2026, 28, 34, 37, 4245, 70, 75, 87, 9194, 128.
Figure 3Chart of ethnic categories which fall under the NIH term of “Black”. Note: Data from references 11, 15, 16, 19, 2633, 3537, 40, 46, 47, 49, 50, 70, 75, 79, 87, 9497, 129, 130.
…”
Section: Methodsmentioning
confidence: 99%
“…They are intended for the visualization of the complexity of ethnic categorization in pharmacogenetics literature and only reflect how these ethnic categories were classified in the literature we reviewed. A full list of ethnic categories included in this study can be found in Table S2 .
Figure 1Chart of ethnic categories which fall under the NIH term of “Asian”. Note: Data from references 7, 8, 10, 12, 14, 16, 28, 37, 41, 42, 48, 51, 7173, 8790.
Figure 2Chart of ethnic categories which fall under the NIH term of “Caucasian”. Note: Data from references 9, 11, 13, 18, 2026, 28, 34, 37, 4245, 70, 75, 87, 9194, 128.
Figure 3Chart of ethnic categories which fall under the NIH term of “Black”. Note: Data from references 11, 15, 16, 19, 2633, 3537, 40, 46, 47, 49, 50, 70, 75, 79, 87, 9497, 129, 130.
…”
Section: Methodsmentioning
confidence: 99%
“…prostate cancer in men of African descent (Metcalfe et al 2008;Williams and Powell 2009;Chornokur et al 2011;Farrell et al 2013;Martin et al 2013;Powell and Bollig-Fischer 2013). The disease burden among migrant populations too are constantly evolving and the impact of Westernisation and globalisation means that there are new healthcare challenges that could be addressed through studying genomic variation (Garduño-Diaz and Khokhar 2012; Dubé et al 2015;Barlas et al 2016).…”
Section: Why Does This Matter?mentioning
confidence: 99%